2007
DOI: 10.1002/cne.21476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rds abundance on cone outer segment morphogenesis, photoreceptor gene expression, and outer limiting membrane integrity

Abstract: We examined the molecular, structural, and functional consequences on cone photoreceptors of the neural retinal leucine zipper knockout (Nrl −/− ) mice when only one allele of retinal degeneration slow (Rds) is present (Rds +/− /Nrl −/− ). Quantitative RT-PCR and immunoblot analysis were used to assess the expression levels of several phototransduction genes; electroretinography was used to assess quantitatively the retinal responsiveness to light; and immunohistochemistry and ultrastructural analysis were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 32 publications
3
37
0
Order By: Relevance
“…Retinal degeneration slow (rds 2/2 ) mutant mice (in the roddominant wild-type background) fail to develop OSs and have no detectable retinal function (4 -6). In contrast, we have reported that cones lacking RDS (in the cone-dominant neural retina leucine zipper knockout, nrl 2/2 , background) (7 -9) retain some OS function and structure, albeit abnormal (3,10). This divergence in the role of RDS in rods versus cones is underscored by the observation that mutations in the human Rds gene are associated with a variety of rod-or conedominant blinding retinal diseases, including autosomal dominant retinitis pigmentosa and multiple classes of macular degeneration (11,12).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Retinal degeneration slow (rds 2/2 ) mutant mice (in the roddominant wild-type background) fail to develop OSs and have no detectable retinal function (4 -6). In contrast, we have reported that cones lacking RDS (in the cone-dominant neural retina leucine zipper knockout, nrl 2/2 , background) (7 -9) retain some OS function and structure, albeit abnormal (3,10). This divergence in the role of RDS in rods versus cones is underscored by the observation that mutations in the human Rds gene are associated with a variety of rod-or conedominant blinding retinal diseases, including autosomal dominant retinitis pigmentosa and multiple classes of macular degeneration (11,12).…”
Section: Introductionmentioning
confidence: 94%
“…The methods employed for tissue collection and processing for plastic-embedment light and electron microscopy and immunogold labeling were as described previously (3,10,15). For light microscopy, 0.75 mm sections were viewed and photographed with an Olympus BH-2 photomicroscope with a Nikon digital camera system.…”
Section: Histology Transmission Electron Microscopy and Immunogold Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in rds 2/2 /Nrl 2/2 mice have highlighted the differential role of peripherin-2 in rods and cones. In contrast to rods lacking peripherin-2 (in the WT background), cones lacking peripherin-2 (in the rds 2/2 /Nrl 2/2 mice) form OSs, albeit dysmorphic ones (Farjo et al 2006b(Farjo et al , 2007. These OSs lack the elaborate folded lamellae structure of normal cones and have no rims at all, but nonetheless retain the ability to mediate phototransduction.…”
Section: Prph2 Gene Therapymentioning
confidence: 99%
“…Eyes were fixed in Davidson's fixative [30 mL of 95% (v/v) ethanol, 20 mL of 10% neutral buffered formalin, 10 mL of glacial acetic acid and 30 mL of distilled water] overnight at 4 °C (28). The eyes were then washed three times in phosphate-buffered saline (PBS) and stored in 70% ethanol for subsequent serial dehydration and embedment in paraffin.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%